Świat jako tranzyt. Poetyka przestrzeni w poezji Gizelli Lachman - Brzykcy, Jolanta (Studia Rossica Posnaniensia, 2021)
The article is an analysis of the poetry of Gisella Lachman (1895–1969), poet of the “first wave” of Russian emigration, from the perspective of the poetics of space. The poet expressed her emigration experience (multiple changes of residence: Russia, Germany, Switzerland, USA) in her poems in spatial relations. They appear on different levels of the works’ morphology: in the construction of the lyrical “I”, in the organisation of the presented world, in the repertoire of motifs and the selection of poetic lexis and genre forms. Space plays a literal role in Lachman’s poetry; it is a representation of extra-literary reality, seen subjectively. It is also subject to metaphorisation, becoming a tool for expressing philosophical content. The poet creates not only a spatial model of the world, but also a spatial model of human life, which she perceives as a transit on the road to eternity.